Bacteriocins as antimicrobial and preservative agents in food: Biosynthesis, separation and application. (April 2022) - Verma, Deepak Kumar; Thakur, Mamta; Singh, Smita; Tripathy, Soubhagya; Gupta, Alok Kumar; Baranwal, Deepika; Patel, Ami R.; Shah, Nihir; Utama, Gemilang Lara; Niamah, Alaa Kareem; Chávez-González, Mónica L.; Gallegos, Carolina Flores; et al.
Abstract: Emerging evidence shows the trend of using safe and natural preservatives like bacteriocins in food processing. The increasing demand by the food industry to extend keeping quality and prevent spoilage of various food products has appealed for new preservatives and new methods of conservation. Further, to discover the novel spectrum of antimicrobial compounds that could effectively battle food-borne pathogens, bacteriocins have been intensively studied in the last few years. Recently, great attention has been paid to the application of lactic acid-bacterial bacteriocins targeting food spoilage-causing or pathogenic microorganisms with no significant side effects. Different mechanisms of action like pore-formation, retarding cell-wall/nucleic acid/protein synthesis have been proposed and described for diverse bacteriocins. Therefore, the syntheses, purification of bacteriocins in addition to their applications as antimicrobial and preservative agents in food processing are reviewed in detail. The review will also discuss the preservative effect of bacteriocins and their combinations having multiple modes of action (hurdle approach) to reduce the microbial load as well as antimicrobial resistance. Graphical abstract: Image 1 Highlights: Bacteriocins are low molecular ribosomal active peptides formed from microorganisms. Purification of bacteriocins is a big challenge. They possess antimicrobial properties against Gram positive & Gram negative bacteria. They are promising preservative in food products than their chemical counterparts. Genetic engineering can design bacteriocins with better antimicrobial resistance.